The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ange.201810327
|View full text |Cite
|
Sign up to set email alerts
|

Katalysatorfreie enantiospezifische Olefinierung mithilfe von in situ generierten Organocer‐Spezies

Abstract: Wirb eschreiben die In-situ-Synthese von Triorganocer-Reagentien und deren Anwendung in katalysatorfreien Zweifel-Olefinierungen. Diese einzigartigen Cer-Spezies wurden durch neuartige Austauschreaktionen von Organohalogeniden mit n-Bu 3 Ce-Reagentien erzeugt. Durch die geeignete Elektronegativitätv on Cer konnten sowohl die Empfindlichkeit von Organolithium-Verbindungen fürfunktionelle Gruppen als auch die geringere Reaktivitätv on Organomagnesium-Verbindungen ausgeglichen werden. Austauschreaktionen wurden a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Theresult with the iodoester derivative 4i is particularly instructive,since such substituents were not tolerated in halogen-lanthanum exchange reactions,showing that organosamariums are better compatible with more sensitive functional groups than the corresponding organolanthanum derivatives. [11] This observation is as trong argument in favor of ad ependence of the functional group compatibility on the ionic character of the carbon-metal bond. Finally,2-iodothiophene (4j), and 3-iodopyridine (4k), and 3-iodoindole (4l)r eacted with nBu 2 SmCl·4 LiCl (1, 0.60 equiv), furnishing diheteroarylsamarium derivatives 5jl,w hich were further transformed into alcohols 6j-l in 83-85 %y ield (Scheme 3).…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Theresult with the iodoester derivative 4i is particularly instructive,since such substituents were not tolerated in halogen-lanthanum exchange reactions,showing that organosamariums are better compatible with more sensitive functional groups than the corresponding organolanthanum derivatives. [11] This observation is as trong argument in favor of ad ependence of the functional group compatibility on the ionic character of the carbon-metal bond. Finally,2-iodothiophene (4j), and 3-iodopyridine (4k), and 3-iodoindole (4l)r eacted with nBu 2 SmCl·4 LiCl (1, 0.60 equiv), furnishing diheteroarylsamarium derivatives 5jl,w hich were further transformed into alcohols 6j-l in 83-85 %y ield (Scheme 3).…”
mentioning
confidence: 95%
“…[7] Besides ate-metal reagents such as manganates [8] and cuprates [9] undergo an exchange, but the atom economy [10] of these reactions is moderate.Recently,w eh ave reported an ew halogen/lanthanum exchange reaction and have found that this exchange is at least 10 6 faster than the halogen/magnesium exchange.A lso, the I/La or Br/La exchange displays better functional group tolerance than the halogen/lithium exchange. [11] This led us to postulate that the rate of the halogen/metal exchange depends on the ionic character of the carbon-metal bond of the exchange reagent, and that the functional group compat-ibility also depends on this ionic character and therefore on the electronegativity [12] of the metal (Scheme 1).Forp roving this relation, we turned our attention to samarium which has an electronegativity of 1.17 compared to 1.10 for lanthanum. We therefore predicted that the halogen/ samarium exchange should be slower than the halogen/ lithium, the halogen/lanthanum, and the halogen/cerium exchanges,a nd that the functional group tolerance of the resulting arylsamarium(III) reagent should be better than that of the corresponding lanthanum(III) reagents.Moreover, organosamarium reagents already proved their utility as nucleophiles,b ut only few preparation methods of these organometallics have been reported.…”
mentioning
confidence: 99%
See 3 more Smart Citations